2019
DOI: 10.3389/fendo.2019.00811
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxidative Stress on Age-Associated Decline in Oocyte Developmental Competence

Abstract: Reproductive capacity in women starts to decline beyond their mid-30s and pregnancies in older women result in higher rates of miscarriage with aneuploidy. Age-related decline in fertility is strongly attributed to ovarian aging, diminished ovarian reserves, and decreased developmental competence of oocytes. In this review, we discuss the underlying mechanisms of age-related decline in oocyte quality, focusing on oxidative stress (OS) in oocytes. The primary cause is the accumulation of spontaneous damage to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(140 citation statements)
references
References 94 publications
5
116
0
Order By: Relevance
“…The aging of postovulatory oocytes has a significant negative impact on livestock production. Although the mechanism of aging is not yet fully clear, excessive accumulation of ROS is considered to be a major factor in inducing aging ( Cui et al, 2011 ; Sasaki et al, 2019 ; Tamura et al, 2020 ). Here, our results demonstrated that IMP exhibited antioxidant effects and enhanced aged oocyte quality by reducing ROS accumulation, autophagy, and apoptosis, enhancing mitochondrial function, and subsequently promoting embryonic development ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aging of postovulatory oocytes has a significant negative impact on livestock production. Although the mechanism of aging is not yet fully clear, excessive accumulation of ROS is considered to be a major factor in inducing aging ( Cui et al, 2011 ; Sasaki et al, 2019 ; Tamura et al, 2020 ). Here, our results demonstrated that IMP exhibited antioxidant effects and enhanced aged oocyte quality by reducing ROS accumulation, autophagy, and apoptosis, enhancing mitochondrial function, and subsequently promoting embryonic development ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…From both a scientific and clinical point of view, the analysis of the effects of oxidative stress on female fertility represents a topic of great interest [ 6 , 24 ]. A great deal of research has shown a contributory role of follicular fluid ROS on ovarian aging and consequently, on oocyte quality [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is the biological consequence of aging, implicated in a variety of age-associated diseases. The increased vulnerability of oocytes to age-induced oxidative stress is associated with the attenuation of the efficacy of DNA double-strand break (DSB) repair mechanisms in aged oocytes [ 142 ]. Some studies have been conducted to correlate follicular fluid extracellular miRNA with advanced women age.…”
Section: Potential Of Mirnas In Aging and Related Disordersmentioning
confidence: 99%